2017
DOI: 10.1124/dmd.116.074567
|View full text |Cite
|
Sign up to set email alerts
|

Considerations from the IQ Induction Working Group in Response to Drug-Drug Interaction Guidance from Regulatory Agencies: Focus on Downregulation, CYP2C Induction, and CYP2B6 Positive Control

Abstract: The European Medicines Agency (EMA), the Pharmaceutical and Medical Devices Agency (PMDA), and the Food and Drug Administration (FDA) have issued guidelines for the conduct of drug-drug interaction studies. To examine the applicability of these regulatory recommendations specifically for induction, a group of scientists, under the auspices of the Drug Metabolism Leadership Group of the Innovation and Quality (IQ) Consortium, formed the Induction Working Group (IWG). A team of 19 scientists, from 16 of the 39 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(64 citation statements)
references
References 100 publications
5
59
0
Order By: Relevance
“…34,35 The study of downregulation of drug-metabolizing enzymes presents a few challenges, some of which include (1) variability in drug response in human hepatocyte experiments partly due to differences in culture conditions; (2) loss of enzymatic activity in hepatocyte cultures over time; (3) lack of positive controls for downregulation; and (4) the facts that observed changes in mRNA may be due to cytotoxicity, and in vitro findings do not always translate into clinical effects. 39 The prolonged change in pharmacokinetics observed in our study is similar to those previously reported in DDIs with warfarin 8,10 and other CYP2C9 substrates, 27,28 and transcriptional changes can take time to disappear. We were unable to find a suitable nonclinical model to study an event that takes this long to manifest.…”
Section: Discussionsupporting
confidence: 90%
“…34,35 The study of downregulation of drug-metabolizing enzymes presents a few challenges, some of which include (1) variability in drug response in human hepatocyte experiments partly due to differences in culture conditions; (2) loss of enzymatic activity in hepatocyte cultures over time; (3) lack of positive controls for downregulation; and (4) the facts that observed changes in mRNA may be due to cytotoxicity, and in vitro findings do not always translate into clinical effects. 39 The prolonged change in pharmacokinetics observed in our study is similar to those previously reported in DDIs with warfarin 8,10 and other CYP2C9 substrates, 27,28 and transcriptional changes can take time to disappear. We were unable to find a suitable nonclinical model to study an event that takes this long to manifest.…”
Section: Discussionsupporting
confidence: 90%
“…After treatment of patients with rheumatoid arthritis with anti-IL-6 antibodies, the exposure of CYP2C9, CYP2C19, and CYP3A4 substrates decreased. 27,28 However, existing information 5,23 coupled with the data collected in this study, suggests that unlike cytokine-mediated CYP downregulation, small molecule-mediated CYP downregulation in vitro does not necessarily translate to in vivo decreases in enzyme activity. It is likely that the lack of translation of in vitro downregulation to in vivo DDI is dependent on the mechanism of regulation of enzyme expression, and more studies are needed to identify mechanisms of CYP downregulation.…”
Section: Discussionmentioning
confidence: 88%
“…On study day 2, subjects were given 13cisRA to be taken as 40 mg b.i.d. with food for 13 days (study days [2][3][4][5][6][7][8][9][10][11][12][13][14]. The 13cisRA capsules were purchased (as Isotretinoin) by the University of Washington Investigational Pharmacy, which dispensed all study medications.…”
Section: Prediction Of Ddismentioning
confidence: 99%
See 1 more Smart Citation
“…A screening method for CYP induction often uses 96‐well plated HHEP (e.g., 70,000 cells at seeding), includes 2‐day treatment with test compound at three concentrations (e.g., 1, 10, and 100 μM, if solubility allows), and measures mRNA and activity changes of the enzymes (Table , Figure ) (Fahmi, Kish, Boldt, & Obach, ; Hariparsad et al, ; Kenny et al, ; Sane et al, ). Positive controls of 20 μM of omeprazole for CYP1A2, 1 mM phenobarbital for CYP2B6, and 10 μM rifampin for CYP3A4 are typically used in induction screening experiments.…”
Section: Mechanisms On How Perpetrators Alter Pharmacokinetics Of Vicmentioning
confidence: 99%